Intraneuronal accumulation of amyloid-β peptides as the pathomechanism linking autism and its co-morbidities: epilepsy and self-injurious behavior — the hypothesis - Frackowiak, Janusz; Mazur-Kolecka, Bozena (Frontiers in Molecular Neuroscience, 2023)
Autism spectrum disorder (ASD) is associated with enhanced processing of amyloid-β precursor protein (APP) by secretase-α, higher blood levels of sAPPα and intraneuronal accumulation of N-terminally truncated Aβ peptides in the brain cortex — mainly in the GABAergic neurons expressing parvalbumin — and subcortical structures. Brain Aβ accumulation has been also described in epilepsy—the frequent ASD co-morbidity. Furthermore, Aβ peptides have been shown to induce electroconvulsive episodes. Enhanced production and altered processing of APP, as well as accumulation of Aβ in the brain are also frequent consequences of traumatic brain injuries which result from self-injurious behaviors, another ASD co-morbidity. We discuss distinct consequences of accumulation of Aβ in the neurons and synapses depending on the Aβ species, their posttranslational modifications, concentration, level of aggregation and oligomerization, as well as brain structures, cell types and subcellular structures where it occurs. The biological effects of Aβ species which are discussed in the context of the pathomechanisms of ASD, epilepsy, and self-injurious behavior include modulation of transcription—both activation and repression; induction of oxidative stress; activation and alteration of membrane receptors’ signaling; formation of calcium channels causing hyper-activation of neurons; reduction of GABAergic signaling — all of which lead to disruption of functions of synapses and neuronal networks. We conclude that ASD, epilepsy, and self-injurious behaviors all contribute to the enhanced production and accumulation of Aβ peptides which in turn cause and enhance dysfunctions of the neuronal networks that manifest as autism clinical symptoms, epilepsy, and self-injurious behaviors.